Implikasi Music therapy sebagai bentuk katarsis dan relaksasi emosi (Implications of Music Therapy as a Form of Catharsis and Emotional Relaxation) - Syarifani, Nara (Happiness: Journal of Psychology and Islamic Science, 2024)
Humans have a fundamental need to express and manage their emotions. Musik therapy, a therapeutic intervention that utilizes music, offers significant potential in helping individuals achieve emotional balance. Research suggests that music therapy can serve as a form of emotional catharsis and relaxation, providing benefits to individuals' mental health and well-being. This research used a comprehensive literature insight to analyse a range of scientific studies examining the effectiveness of music therapy in the context of emotional catharsis and relaxation. Data were collected from various sources, including academic journals, research databases and scholarly books. The literature review showed that music therapy has significant potential in facilitating the process of emotional catharsis and relaxation. Through various mechanisms, such as emotional stimulation, stres reduction, and improved emotion regulation, music therapy can help individuals express and manage their emotions in a healthy manner. Research shows that music therapy can provide positive mental health benefits, such as the reduction of anxiety, depression, and trauma, as well as improved well-being and quality of life. As a form of emotional catharsis and relaxation, music therapy offers significant potential to improve the mental health and well-being of individuals.